Relasi Santri Dan Kiai Di Pesantren Afiliasi NU (Antara Kultur Etika Islam Dan Aristokrasi Warisan) - Hakim, Abdul; Zainul Arif, Moh. (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This article purpose to examine and criticize the tradition of relations between santri and kiai in Islamic boarding schools which are generally affiliated with Nahdlatul Ulama (NU). NU is likened to a large Islamic boarding school, while the Islamic boarding schools scattered throughout the archipelago are miniatures of NU. NU's progress and contributions are very diverse and are felt to this day, especially the struggle to expel the invaders in the archipelago, culminating in the momentum of the November 10 battle in Surabaya through the Jihad Fatwa (Resolution) issued by KH. Hasyim Asy'ari as Rais Akbar NU at that time. Another contribution of NU that has had a broad impact in the field of education is the existence of Islamic boarding schools which are estimated to have emerged in the 16th century AD. Islamic boarding school education is native to the archipelago and is claimed to be the oldest education system. Apart from being taught religious sciences such as jurisprudence, faith and morals, character education is also strongly instilled in Islamic boarding schools through direct education from a kiai. However, in practice, there is often an excessive cult of kiai due to several underlying factors, highlighted here is the aristocracy tradition inherited from the palace which is reflected in the santri's ethics towards kiai.